Mechanism of translation inhibition by type II GNAT toxin AtaT2 - Ovchinnikov, Stepan V (Nucleic Acids Res, 2020)
Type II toxin–antitoxins systems are widespread in prokaryotic genomes. Typically, they comprise two proteins, a toxin, and an antitoxin, encoded by adjacent genes and forming a complex in which the enzymatic activity of the toxin is inhibited. Under stress conditions, the antitoxin is degraded liberating the active toxin. Though thousands of various toxin–antitoxins pairs have been predicted bioinformatically, only a handful has been thoroughly characterized. Here, we describe the AtaT2 toxin from a toxin–antitoxin system from Escherichia coli O157:H7. We show that AtaT2 is the first GNAT (Gcn5-related N-acetyltransferase) toxin that specifically targets charged glycyl tRNA. In vivo, the AtaT2 activity induces ribosome stalling at all four glycyl codons but does not evoke a stringent response. In vitro, AtaT2 acetylates the aminoacyl moiety of isoaccepting glycyl tRNAs, thus precluding their participation in translation. Our study broadens the known target specificity of GNAT toxins beyond the earlier described isoleucine and formyl methionine tRNAs, and suggest that various GNAT toxins may have evolved to specificaly target other if not all individual aminoacyl tRNAs.